Hybrid Materials for Functional 3D Printing. Issue 22 (19th October 2018) - Cooperstein, Ido; Sachyani‐Keneth, Ela; Shukrun‐Farrell, Efrat; Rosental, Tamar; Wang, Xiaofeng; Kamyshny, Alexander; Magdassi, Shlomo
Abstract: This review focuses on the development of hybrid materials based on inorganic–organic compositions with improved and new functionalities, and their utilization for 3D printing of various devices: magnetic materials, flexible and stretchable materials for conductive and shape‐memory devices, materials for photonics and optics, materials with enhanced mechanical properties, and dielectric and piezoelectric materials. Various methods of functional 3D printing are briefly discussed. Abstract : 3D printing and compositions of hybrid materials based on inorganic–organic compositions are presented. The resulting 3D hybrid objects are improved and new functionalities, such as enhanced mechanical and optical properties are introduced. These materials can be utilized for 3D printing of various devices, such as magnetic actuators, flexible and stretchable conductors. Various methods of functional 3D printing are briefly discussed.